2012
DOI: 10.1002/term.1456
|View full text |Cite
|
Sign up to set email alerts
|

Anin vivostudy on the effect of scaffold geometry and growth factor release on the healing of bone defects

Abstract: The hypothesis of this study was that the extent of bone regeneration could be enhanced by using scaffolds with appropriate geometry, and that such an effect could be further increased by mimicking the natural timing of appearance of bone morphogenetic proteins BMP-2 and BMP-7 after fracture. Bioplotted poly(ε-caprolactone) (PCL) disks with four different fibre organizations were used to study the effect of 3D scaffold architecture on the healing of bone defects in a rat pelvis model. Moreover, one PCL constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…No residual hydrogel was detected by MRI with in situ polymerized PFGdDTPA-Cy5.5 on the third week of the experiment. These results are consistent with previous studies that use other techniques to document how in vivo fate of biomaterial implants is dependent on the composition, dimensions, in situ environment, and degradation products (13,15,(26)(27)(28). In the context of hydrogel biomaterial implants specifically, the MRI results are in close agreement with the work of Artzi et al (15); they also showed that implant geometry significantly affects the in vivo degradation patterns of the implant.…”
Section: Significancesupporting
confidence: 91%
See 3 more Smart Citations
“…No residual hydrogel was detected by MRI with in situ polymerized PFGdDTPA-Cy5.5 on the third week of the experiment. These results are consistent with previous studies that use other techniques to document how in vivo fate of biomaterial implants is dependent on the composition, dimensions, in situ environment, and degradation products (13,15,(26)(27)(28). In the context of hydrogel biomaterial implants specifically, the MRI results are in close agreement with the work of Artzi et al (15); they also showed that implant geometry significantly affects the in vivo degradation patterns of the implant.…”
Section: Significancesupporting
confidence: 91%
“…Although VEGF has been used exogenously to promote in vivo angiogenesis, superior results were obtained when the factor was protected, localized, and temporally controlled at the site of implantation (7,10,11). The hypothesis underlying this study is that degradation and resorption characteristics of the implant may be influenced by its surface area-to-volume ratio and mode of implantation, and hence the release properties of the proangiogenic factors within the implant site can be optimized accordingly (12)(13)(14)(15). As a case in point, an injectable strategy whereby the hydrogel precursor solution is injected and crosslinked in situ allows an even and contiguous dispersion of the hydrogel within the injury interstitial space for better host integration.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…25 In the present study, in order to monitor the loading in the gelatin film and release out of this film of a growth factor mixture and proteins from serum, we performed a bottom-up proteomic analysis using capillary electrophoresis (CE) coupled to electrospray ionization mass spectrometry (ESI-MS) 26 (Table 1 in the ESI †). 25 In the present study, in order to monitor the loading in the gelatin film and release out of this film of a growth factor mixture and proteins from serum, we performed a bottom-up proteomic analysis using capillary electrophoresis (CE) coupled to electrospray ionization mass spectrometry (ESI-MS) 26 (Table 1 in the ESI †).…”
Section: Loading and Release Of Serum Componentsmentioning
confidence: 99%